Privatization Incentives: A Wage Bargaining Approach - Andreas Kuhlmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
We analyze the incentives of a government to privatize a state owned firm. Assumingprice cap regulation, a unionized labor market and wage bargaining the governmentsgains from privatization depend on two effects. While the government looses controlover the firms investment and employment decisions, the unions bargaining positioncan be weakened by privatization. Since price cap regulation tends to increase the wage under privatization, the governments incentives to privatize are low if the unions bargaining power is high. Considering different kinds of in-vestments does not change this result qualitatively.
Keywords: H32; L32; L33; 330; Wage bargaining regulation privatization